Arthur plays the blues - Krensky, Stephen; Lieuwen, Catherine (New York : Little, Brown and Co., 2003)
When Arthur fails to show up for his second piano lesson, his music teacher dismisses him. Now Arthur has to decide how much he wants to learn to play the piano.
420
Accelerated Reader AR
Keywords: Music -- History and criticism -- Juvenile literature; Aardvark -- Juvenile fiction